SPH analysis of collisions between macroscopic bodies immersed in planetary rings - Siqueira, Patricia Buzzatto [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Planetary rings, a common feature around giant planets, have recently been discovered around centaurs and dwarf planets. These rings often contain azimuthally confined structures known as arcs, associated with increased particle density due to corotation resonances. One well-known example is Saturn's G ring arc, attributed to the Aegaeon satellite's presence and the resonant confinement by Mimas. However, the conventional explanation of dust production by Aegaeon struggles to account for the arc's brightness within the observed period. Our study explores an alternative model of dust generation within planetary rings. Building upon that some of those systems could have macroscopic bodies, below the resolution limit of cameras and have the potential to collide, generating the visible dust or even forming new satellites. For studying the impacts between the macroscopic bodies, we used Smooth Particle Hydrodynamics (SPH) by performing detailed simulations including shock propagation, material modification and gravitational reaccumulation. Unlike previous approaches that assume gravitational regimes \cite{Leinhardt2011}, we consider a wide range of body sizes, making no geometric constraints on collisions. This approach includes physical properties like fragmentation and porosity that cannot be addressed through N-body simulations alone. Incorporating these properties, we model the collision outcomes, exploring how bodies with such characteristics deform, compress, or fracture based on various strength models. The results of these simulations are critical for understanding the dust production and longevity of objects within planetary rings. Comparing multiple strength models ensures the accuracy of the simulations. The unique properties of planetary ring particles, including mixed ice-rock composition, high porosity, and low material strength, present computational challenges. Our research addresses these challenges by employing a hybrid method, combining detailed SPH simulations with analytical models and N-body simulations to estimate dust production rates. Overall, this work offers a comprehensive approach to understanding dust generation within planetary rings, shedding light on the dynamics and physical properties of macroscopic bodies immersed in planetary rings.
Análise SPH de colisões entre corpos macroscópicos imersos em anéis planetários
Keywords: SPH; planetary ring; G arc; collisions; macroscopic bodies; Planetas - Órbitas; Poeira cósmica; Satélites; Sistema solar